The effect of temperature on the leaching of Cr, Cu, Fe, Ni and Zn from tailings, Ballangen deposit, Norway - Lu, Jinmei; Yuan, Fuqing; Leiviska, Tiina (International Journal of Environmental Impacts: Management, Mitigation and Recovery, 2019)
In this study, the effect of temperature on the leaching of Cr, Cu, Fe, Ni and Zn from oxidized tailings, Ballangen deposit, Norway, was investigated by a laboratory batch leaching experiment. The leaching was conducted at four different temperatures 5°C, 10°C, 15°C and 20°C and 2 precipitation rates of 8 mm/week and 20 mm/week. The leachates from six leaching cycles were collected, and the concentra- tions of Cr, Cu, Fe, Ni and Zn were tested. The results showed that at a precipitation rate of 20 mm/ week, the leached amount of Cr, Fe, Cu was highest at a leaching temperature of 20°C and the lowest leached amount for Cr was observed at 10°C. 10°C seems to be a threshold temperature for the leaching of Cr. However, at a precipitation rate of 8 mm/week, the highest leached amount of Cr, Fe and Cu was observed at 5°C and the lowest leached amount for Cr and Fe was observed at 20°C. The relationship between the accumulated leached amount of Cr, Cu, Fe, Ni and Zn and leaching water volume was ap- proximated by a logarithmic function at different temperatures. If the factor of precipitation is ignored, only the accumulated leached amount at different temperatures is considered. The accumulated leached amount of Cr, Fe and Cu is highest at a leaching temperature of 20°C, which is significantly higher than that at other leaching temperatures by the established statistical model. The accumulated leached amount of Ni at 15°C and 20°C is significantly higher than that at 5°C and 10°C. The accumulated leached amount of Zn was highest at a leaching temperature of 10°C, which was significantly higher than that at 15°C and 20°C by the statistical model. Zn tends to be leached out at low temperatures.